Identifying and prioritizing evidence needs in self-care interventions for sexual and reproductive health - Sedgh, Gilda; Sorhaindo, Annik (Frontiers in Global Women's Health, 2023)
Background: Self-care as an extension of health care systems can increase access to care. The development of programs and generation of evidence to support self-care in sexual and reproductive health (SRH) is a relatively nascent field. We undertook a study to identify and prioritize evidence gaps for SRH self-care. Methods: We used the CHNRI methodology and administered two online surveys to stakeholders affiliated with major self-care networks. The first survey was used to identify evidence gaps, and the second to prioritize them using predetermined criteria. Results: We received 51 responses to the first survey and 36 responses to the second. Many evidence gaps focused on awareness of and demand for self-care options and best mechanisms for supporting users of self-care with information, counseling and linkages to care. Conclusion: A priority area of work ahead should be determining which aspects of the learning agenda reflect gaps in evidence and which reflect a need to effectively synthesize and disseminate existing evidence.